Evidence for allocentric boundary and goal direction information in the human entorhinal cortex and subiculum - J. P. Shine (Nature Portfolio, 2019)
In rodents, cells in the medial entorhinal cortex and subiculum are known to encode the allocentric direction to nearby walls and boundaries. Here, using fMRI the authors show that this is also true in humans, with allocentric boundary direction being encoded in posterior entorhinal cortex and subiculum.